The Information Communication Technology, Social Media, International Migration and Migrants’ Relations with Kin in Nigeria - Akanle, Olayinka; Fayehun, OA; Oyelakin, S (Journal of Asian and African studies (Leiden), 2021)
Studies abound on international migration and remittances across the world and studies are particularly not lacking on the subject in Africa. There are however few studies on the moderating roles of information communication technology (ICT) and social media in the relationships among international migration, remittances and relationships in Sub-Saharan Africa. This article examines the dimension of ICT and social media in migration studies. This is an aspect that has often been ignored and overlooked even though ICT and social media have great contributions in the international migration process particularly as migrants and relatives in sending and receiving countries both have the primary experience. Research objectives include: reasons for emigration; information technology/social media used by migrants and their kin as they relate across spaces; and how ICT affects relationships of kin and international migrants. Secondary data were gathered through journals, books, documents and reliable Internet sources. Primary data were gathered in Ibadan, Nigeria in 2018 through 30 in-depth interviews analysed through content analysis. Findings reveal the nature of ICT used by international migrants and their kin and purpose of utilization and the effects of ICT on international migration, remittances and kinship networks. The article presents detailed data, narratives, interpretations and implications of relationships among international migration, ICT/social media and kinship networks. This article argues that ICT/social media is central to international migration decision-making, access of migrants and kin to social forces and factors motivating international migration, and it is very important to how migrants and kin maintain and/or weaken relationships and access to remittances and utilization.